2017
DOI: 10.1021/acs.joc.7b02017
|View full text |Cite
|
Sign up to set email alerts
|

Independent Generation and Reactivity of Thymidine Radical Cations

Abstract: Thymidine radical cation (1) is produced by ionizing radiation and has been invoked as an intermediate in electron transfer in DNA. Previous studies on its structure and reactivity have utilized thymidine as a precursor, which limits quantitative product analysis because thymidine is readily reformed from 1. In this investigation, radical cation 1 is independently generated via β-heterolysis of a pyrimidine radical generated photochemically from an aryl sulfide. Thymidine is the major product (33%) from 1 at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
(162 reference statements)
0
11
0
Order By: Relevance
“…Until now, there has been increased attention on the radical cations of DNA bases and their degradation reactions, , among which the radical cation of guanine (G •+ ) has been of great interest because of the lowest oxidation potential of guanine among the four DNA bases (G < A < C < T). Competitive pathways of hydration and deprotonation subsequent to the formation of the G •+ were revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there has been increased attention on the radical cations of DNA bases and their degradation reactions, , among which the radical cation of guanine (G •+ ) has been of great interest because of the lowest oxidation potential of guanine among the four DNA bases (G < A < C < T). Competitive pathways of hydration and deprotonation subsequent to the formation of the G •+ were revealed.…”
Section: Introductionmentioning
confidence: 99%
“…This is also inconsistent with the previously proposed mechanism, but consistent with product studies on monomeric T•+, which showed that fdU formation is a minor product. 20,22…”
Section: Resultsmentioning
confidence: 99%
“…DNA hole migration is initiated by one-electron oxidation of DNA, that is, hole injection, and is a primary consequence of the direct effect of ionizing radiation. Hole injection by chemical and/or photochemical methods takes advantage of the differences in redox potentials to selectively generate the radical cation of 2′-deoxyguanosine (dG) and/or dA. Short wavelength UV-irradiation (≤254 nm) and other forms of ionizing radiation (e.g., γ-radiolysis, photosensitization) are unselective and generate pyrimidine (e.g., T •+ ) and purine radical cations. Nucleotide radical cation formation is a hallmark of the direct effect of ionizing radiation. The role of dG •+ in hole migration and subsequent hole trapping by reacting with H 2 O/O 2 is well documented. , The reactivity of T •+ is less well understood than that of dG •+ and dA •+ , due to the lack of methods to selectively produce the pyrimidine radical cation . Most reports on T •+ reactivity have focused on the nucleoside.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of deprotonation is sensitive to pH and the p K a of the photosensitizer radical anion. The presence of a methyl group at N3 increases the formation of products arising from the hydration pathway in a particular case, suggesting that deprotonation also takes place from the N3 position of the Thd·+ . In the absence of oxygen, the 5‐methyl‐(2′‐deoxyuridylyl) radical undergoes either reduction or oxidation depending on the redox properties of additional compounds .…”
Section: Introductionmentioning
confidence: 99%